Improving the Immune System in Infantile Colic Sufferers - Nur Ain Desta Sulasdi; Mufdlilah; Ismarwati; Hakimi (Postgraduate, University of Mataram, 2024)
Poor sleep quality will lower the immune system, making babies susceptible to illness. Brain maturity is needed for babies to learn various things. Babies with poor sleep quality will reduce the immune system, so that babies are easily sick, including prolonged crying babies will certainly affect the quality of baby sleep. To determine the effectiveness of baby massage on the quality of sleep of infantile colic babies in North Gorontalo Regency, Gorontalo Province. Non-equivalent quasi-experiment research with quantitative approach and two-group pre-test-posttest control group design. Determination of participants based on purposive sampling technique, namely colicky infants with a normal birth weight of 2500 grams - 4000 grams aged 1 to 6 months. The research instrument used observation sheets and questionnaires. Statistical tests used the Wilcoxon test, Mann-Whitney test, and ordinal logistic regression test. Sleep quality of infantile colic infants before being given baby massage intervention there was 1 baby with 2.9% in the good category. After the massage, the data showed that the baby's sleep quality increased in the